Minimal invasive resurfacing: an innovative technique for the superior semicircular canal dehiscence. A case series. Issue 5 (31st May 2022) - Salvinelli, Fabrizio; Bonifacio, Francesca; Beccaria, Claudia; Greco, Fabio; Frari, Valeria; Iafrati, Francesco; Trivelli, Maurizio
Abstract: The superior semicircular canal dehiscence is a vestibular disease recognized condition in recent years, and surgical therapy has been modeling itself over the years to ensure the control of vestibular symptoms and auditory symptoms. In this case series, the authors have experienced an intervention aimed at closing the superior semicircular canal dehiscence through the insertion of bone paté between the meninx and the residual middle cranial fossa bone wall. Seven patients underwent this intervention, they reported an improvement in all vestibular and auditory symptoms, and hearing threshold remained stable. Despite the small sample size, the difference was significant in the control of dizziness and the reduction of pulsatile tinnitus. The technique described in this article allows the control of symptoms in superior semicircular canal dehiscence, and it is a type of surgery familiar to the otosurgeon and easily replicable as it involves a modified mastoidectomy. More data are needed.